Multimedia Interaktif Dalam Pembelajaran Pengaturcaraan Awalan - Abd. Latiff, Abdul Rahman (2000)
The usage of information technology (IT) in education are increasing accepted in Malaysia. Multimedia oriented application are being used widely beginning at a primary school up to the higher institution. Research based on literature reviews, indicates the need for preparing model of multimedia interactive oriented in learning Pengaturcaraan Awalan to fulfill the request of learning based on computer and to arrest the need for a computer based training facility in Malaysia. Lecturers and trainers can use this model to produce computer based training software. This paper focused on the development process of multimedia courseware prototype for the Pengaturcaraan Awalan subject. Techniques from both education and information technology field were combined to produce a good framework of this multimedia learning system. Interactive interface, tutoring strategy and artificial intelligent characteristic are used in developing this courseware. Model of instruction, student and tutor were designed, developed, and used in this prototype.